Integrating clinical pharmacists in care management for secondary stroke prevention clinical trials: a scoping review - Thurston, James; Li, Hanlin; Kronish, Ian M.; Naqvi, Imama A. (Frontiers in Neurology, 2025)
IntroductionClinical pharmacist (CP) integration within interprofessional healthcare team models may effectively provide secondary stroke prevention care and address healthcare disparities.MethodsThis scoping review includes randomized controlled trials (RCTs) that evaluated the effect of interventions inclusive of team-based care by CPs on patient-oriented and health outcomes after stroke or transient ischemic attack (TIA). Search databases included MEDLINE/PubMed, EMBASE, and CINAHL, and ClinicalTrials.gov and the International Standard Randomised Controlled Trial Number (ISRCTN) trial registries. We describe the level of interaction between interprofessional team members, use of telehealth services, population diversity, and intervention effects on study outcomes.ResultsOf 132 RCTs, 14 met inclusion criteria and incorporated CPs in the intervention. These studies were conducted globally and included outcome measures such as medication adherence, morbidity and mortality, and vascular risk factor goal attainment. Twelve trials included multidisciplinary models, while two included interdisciplinary models, and none incorporated transdisciplinary models. Telehealth was leveraged in 8 of 14 trials. One study reported on healthcare disparities associated with poor risk factor control. Positive intervention effects were notable for goal attainment (4 of 10 trials).DiscussionPublished RCTs examining CP impact within secondary stroke prevention teams with limited data suggests that interventions inclusive of CPs delivering medication education, reconciliation, and titration may improve vascular risk factor control, medication adherence, and patient-oriented outcomes. We highlight the need for future secondary stroke prevention clinical trials to provide more insight into CP integration, promote diversity in study populations and clinician roles, and incorporate telehealth to enhance healthcare access.